2011
DOI: 10.2495/wrm110491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation amount and frequency on phenology, vine length and biomass partitioning of wild cucumber (Cucumis myriocarpus) and wild watermelon (Cucumis africanus)

Abstract: This study was conducted to determine the most suitable irrigation frequency and quantity for the greenhouse-grown indigenous leafy vegetable, Cucumis myriocarpus, and herbage crop, Cucumis africanus. Four irrigation intervals were tested, 2, 3, 4 and 5 days, arranged in a randomised complete block design. Total irrigation quantities, plant water consumption, rate of progress towards flowering and vine length varied amongst the irrigation frequency treatments, whereas biomass partitioning to botanical fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This could possibly mean that roots in plants watered twice a week with terminal water stress lost some water during period of no water supply. It has been reported that the more frequently watered Cucumis myriocarpus showed a higher root biomass compared to the less frequently watered plants [18]. Similarly, frequent irrigation (once every month, two months and three months) increased fresh bulb weight of Lycoris haywardii compared to less frequent irrigation (once every four months and six months), which decreased bulb weight by 21% and 52%, respectively [19].…”
Section: Yield Parametersmentioning
confidence: 99%
“…This could possibly mean that roots in plants watered twice a week with terminal water stress lost some water during period of no water supply. It has been reported that the more frequently watered Cucumis myriocarpus showed a higher root biomass compared to the less frequently watered plants [18]. Similarly, frequent irrigation (once every month, two months and three months) increased fresh bulb weight of Lycoris haywardii compared to less frequent irrigation (once every four months and six months), which decreased bulb weight by 21% and 52%, respectively [19].…”
Section: Yield Parametersmentioning
confidence: 99%
“…For example, they often supply most of the daily requirements for vitamins A, B complex and C of poor rural people [1]. To produce enough biomass of high quality which can be converted to leafy vegetable, animal feed and ethno-botanicals, there is need to identify C. myriocarpus production and agronomic management strategies with potential for high biomass yield and specific quality traits [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, most human plant food is based on rather limited number of crops, 12 crops contribute more than 85-90% of world's caloric intake [1]. However, it is clear that in many parts of the world, especially in rural peripheries of developing regions, the use of wild plants is not negligible [2] and warrants greater need for research on crop responses to conventional agronomic methods of production such as integrated irrigation and fertilizer application [3].…”
Section: Introductionmentioning
confidence: 99%